Exploring Role of Organizational Learning, Job Satisfaction and Organizational Commitment on Employee Performance at National Rice Milling Industry - Tannady, Hendy; Veronica, Cindy Lisberth (Journal of Social Science and Business Studies, 2024)
Improving employee performance is the main goal for every organization in achieving sustainable success and growth. Organizational learning, work satisfaction, and organizational commitment are examples of internal elements that must be taken into account in order to attain maximum performance. The purpose of this study is to ascertain how employee performance is affected by organizational learning, job satisfaction, and organizational commitment. The researcher used quantitative research methods, using descriptive research. Employees will be the target population for researchers. Researchers used non-probability sampling, with a sample size of 100 respondents. Data collection was carried out through two main techniques, namely interviews and questionnaires. With the use of smartPLS 3.0 software, the Partial Least Squares (PLS) approach is used for data analysis in this study. Numerous findings were obtained for this study based on the outcomes of the hypothesis testing. Work satisfaction and organizational learning have a strong positive correlation. Organizational learning and organizational commitment have a strong positive correlation. There is no discernible connection between worker performance and organizational learning. There is no discernible link between worker performance and job satisfaction. Employee performance and organizational commitment have a strong positive correlation. As a result, the study's findings help to clarify the variables influencing worker performance, organizational commitment, and job happiness.